ACRE: uma experiência inovadora de Governança? - França, Raimundo Nonato Cunha de (2006)
About two decades ago Brazil has been suffered some important political changes on its government and supporter systems. In these changes the Partido dos Trabalhadores (Workers support) has been researched significant results as much legislation as executive ways. These conquests propitiate a structure for it to get an alternative motion in order to manage public goods by petista government way. Trying to examinate this we can study the Partido dos Trabalhadores government experience in Acre (1999-2002) to know about why the PT government characteristics are different from the others. To do this we assumed to conjecture a popular participation with priorities inversion and ethics in public resources administration. These are the elements of PT government way. This way we started our work making an evaluation of its bibliography. Them we do a field inquiry to analyses documents of the government projects (budget rules law, papers, approved laws, IBGE, PNUD, TSE) and semi-structured interviews with some characters of recent political Acres life. The scheme and the analysis about these givens disclose that weren t confirmed our hypothesis in part, since PT remained old local politics habitus. In other side the executive administration on PT government has got to inflect the Governance . Further on an efficient management as World Bank dispossess but PT absolve many requests of progressive sectors as well it expanded the society participation to resolutions process. By a cabinets enlargement. So it rescues a total administrative course which is printed in the called petista government way. Personally we think so it means important advancements in this Acre government way